Fas–Fas Ligand: Checkpoint of T Cell Functions in Multiple Sclerosis - Volpe, Elisabetta; Sambucci, Manolo; Battistini, Luca; Borsellino, Giovanna (Frontiers in Immunology, 2016)
Fas and Fas Ligand (FasL) are two molecules involved in regulation of cell death. Their interaction leads to apoptosis of thymocytes that fail to rearrange correctly their T cell receptor genes (TCR) and of those that recognize self-antigens, a process called negative selection; moreover, Fas-FasL interaction leads to activation-induced cell death, a form of apoptosis induced by repeated TCR stimulation, responsible for the peripheral deletion of activated T cells. Both control mechanisms are particularly relevant in the context of autoimmune diseases, such as multiple sclerosis (MS), where T cells exert an immune response against self-antigens. This concept is well demonstrated by the development of autoimmune diseases in mice and humans with defects in Fas or FasL. In recent years, several new aspects of T cell functions in MS have been elucidated, such as the pathogenic role of T helper (Th) 17 cells, and the protective role of T regulatory (Treg) cells. Thus, in this review we summarize the role of the Fas-FasL pathway, with particular focus on its involvement in MS, then we discuss recent advances concerning the role of Fas-FasL in regulating Th17 and Treg cells’ functions, in the context of MS.